2015
DOI: 10.7235/hort.2015.14158
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variation in Contents of Sugars in Different Parts of Broccoli

Abstract: Seasonal variation in the contents of sugars (fructose, glucose, and sucrose) in the floret, leaf, and stem of broccoli were studied in ten commercial broccoli cultivars. Plants were grown in the spring and fall seasons in 2011. In both seasons, glucose was the major constituent, comprising about 50% of the total sugar content in the floret and leaf tissue of most cultivars, whereas the broccoli stem showed an unusual pattern of accumulation. Sucrose exhibited greater cultivar dependency as well as seasonal va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
(22 reference statements)
1
4
0
Order By: Relevance
“…The concentrations of the three sugars, glucose, fructose, and sucrose, in cabbage head germplasm during spring and autumn 2019 are shown in Figure 3. Fructose and glucose were the predominant sugars in cabbage germplasm, which concurred with findings from previous studies on cabbage (Rosa et al, 2001;Zhao et al, 2020) and other brassicaceous vegetables such as broccoli and cauliflower (Bhandari and Kwak, 2015a;2015b). In most cases, the germplasm content of glucose was the highest, followed by fructose and sucrose in both growing seasons.…”
Section: Variation In Free Sugar Concentrations and Total Sweetness Isupporting
confidence: 90%
See 3 more Smart Citations
“…The concentrations of the three sugars, glucose, fructose, and sucrose, in cabbage head germplasm during spring and autumn 2019 are shown in Figure 3. Fructose and glucose were the predominant sugars in cabbage germplasm, which concurred with findings from previous studies on cabbage (Rosa et al, 2001;Zhao et al, 2020) and other brassicaceous vegetables such as broccoli and cauliflower (Bhandari and Kwak, 2015a;2015b). In most cases, the germplasm content of glucose was the highest, followed by fructose and sucrose in both growing seasons.…”
Section: Variation In Free Sugar Concentrations and Total Sweetness Isupporting
confidence: 90%
“…Approximately 33% of the genotypes showed higher glucose content in spring than in autumn, whereas the other genotypes showed either higher or similar glucose content in autumn. Bhandari and Kwak (2015a) found higher glucose content in spring than in autumn in 12 broccoli cultivars. Similarly, Rosa et al (2001) observed higher glucose content in cabbage grown in spring than in autumn.…”
Section: Variation In Free Sugar Concentrations and Total Sweetness Imentioning
confidence: 80%
See 2 more Smart Citations
“…The florets in broccoli (Brassica oleracea Italica group) have been shown to contain health beneficial compounds, such as vitamin K and C, minerals, dietary fiber, phenolic compounds, glucosinolates and folic acid [35][36][37]. The broccoli leaves, on the other hand, are not as well studied as the florets, but have been shown to have higher levels of phenolic compounds as compared to the florets [38,39]. The stem in broccoli contains large amount of insoluble fiber and low amounts of soluble fiber [40].…”
Section: Introductionmentioning
confidence: 99%